Physical-mechanical aspects of degradation of heat-echange tubes metal for steam-generators of the type PGW-1000 - Voyevodin, V.N.; Mitrofanov, A.S.; Gozhenko, S.V.; Krainyuk, Y.A.; Vasilenko, R.L.; Bazhukov, A.V.; Paliy, A.N.; Nechipurenko, V.V.; Melnik, P.Y. (Вопросы атомной науки и техники, 2019)
By metallography and scanning electron microscopy the effect of titanium carbonitride and silicon carbide on degradation of steel 08X18H10T was revealed on heat exchanging tubes (HET) of steam generators of powergenerating units of WWER-1000. The role of structural features of steam generators on nucleation and growth of operational defects of HET is shown. За допомогою металографії та растрової електронної мікроскопії встановлено вплив включень карбонитридів титану і карбіду кремнію на деградацію сталі 08Х18Н10Т у теплообмінних трубах (ТОТ) парогенераторів енергоблоків ВВЕР-1000. Показана також роль конструкційних особливостей парогенераторів у зародженні і зростанні експлуатаційних дефектів ТОТ. С помощью металлографии и растровой электронной микроскопии установлено воздействие включений карбонитридов титана и карбида кремния на деградацию стали 08Х18Н10Т в теплообменных трубах (ТОТ) парогенераторов энергоблоков ВВЭР-1000. Показана также роль конструкционных особенностей парогенераторов в зарождении и росте эксплуатационных дефектов ТОТ.